Editorial Note: Sustainable E-Participation - Rolf Lührs; Francesco Molinari (JeDEM - eJournal of eDemocracy & Open Government, 2010)
What makes eParticipation sustainable? This special issue of JeDEM summarises existing evidence and introduces some authoritative viewpoints on a theme that is gaining relevance and furthering discussion among theorists and practitioners alike. This Issue comprises three invited papers and six refereed articles, the results of which will be briefly presented in this note.